2002
DOI: 10.3928/0022-0124-20020701-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Educational Bereavement Program on Health Care Professionals' Perceptions of Perinatal Loss

Abstract: Background: The purpose of this study was to examine the differences in health care professionals' perceptions of perinatal loss situations before and after an educational program on perinatal bereavement. Method: A quasi-experimental design was used in a pretest and posttest format. Results: Scores were significantly higher (p = .000) on each of the posttest vignettes. Overall scores were lowest for the miscarriage pretest, whereas scores for the pretest vignettes for the stillbirth and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The qualities that characterise midwifery care including providing complete information, encouraging self‐determination, and being sensitive to the emotional state are particularly important at a time of loss 8,25 . However, a study on staff perceptions of perinatal loss found that staff viewed miscarriage as not as significant a loss as stillbirth and neonatal loss.…”
Section: Miscarriage As a Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualities that characterise midwifery care including providing complete information, encouraging self‐determination, and being sensitive to the emotional state are particularly important at a time of loss 8,25 . However, a study on staff perceptions of perinatal loss found that staff viewed miscarriage as not as significant a loss as stillbirth and neonatal loss.…”
Section: Miscarriage As a Lossmentioning
confidence: 99%
“…However, a study on staff perceptions of perinatal loss found that staff viewed miscarriage as not as significant a loss as stillbirth and neonatal loss. While an education program on grief and loss theory, professional roles and skills heightened staff's awareness of the impact of miscarriage, it was still seen by them as not as significant 25 …”
Section: Miscarriage As a Lossmentioning
confidence: 99%
“…Perinatal loss is commonly defined as loss of an infant through death via unintended or involuntary loss of pregnancy by miscarriage, early loss (less than 20 weeks), stillbirth (> 20 weeks gestation), or neonatal loss (newborn through 28 days of life) (Robinson et al 1999, DiMarco et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Perinatal bereavement follows perinatal loss; thus it is a global, complex and multifaceted phenomenon that is of concern to nurse clinicians and nurse researchers around the world. Perinatal loss is commonly defined as loss of an infant through death via unintended or involuntary loss of pregnancy by miscarriage, early loss (<20 weeks), stillbirth (>20 weeks gestation) or neonatal loss (newborn through 28 days of life) (Robinson et al 1999, DiMarco et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The care and understanding shown during the time of the loss can influence the parents' grieving process (DiMarco, Renker, Medas, Bertosa, & Goranitis, 2002; Gold, 2007; Säflund, Sjögren, & Wredling, 2004; Trulsson & Rådestad, 2004; Uren & Wastell, 2002). Health care professionals need an understanding of the impact of perinatal loss on subsequent pregnancy so that adequate healthcare may be provided.…”
Section: Introductionmentioning
confidence: 99%